2016
DOI: 10.1159/000447804
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Exposure Enhances Bisphenol A-Induced Genotoxicity through 8-Oxoguanine-DNA Glycosylase-1 OGG1 Inhibition in NIH3T3 Fibroblast Cells

Abstract: Background: Both cadmium (Cd) and bisphenol A (BPA) are commonly encountered in humans' daily activities, but their combined genotoxic effects remain unclear. Methods: In the present study, we exposed a mouse embryonic fibroblast cell line (NIH3T3) to Cd for 24 h, followed by a 24 h BPA exposure to evaluate toxicity. The cytotoxicity was evaluated by viability with CCK-8 assay and lactate dehydrogenase (LDH) release. Reactive oxygen species (ROS) production was measured by 2′,7′-dichlorofluorescein diacetate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…DNA damage for bisphenols was seen in the order of BPS > BPF > BPA. Other researchers have also reported that BPA caused oxidative DNA damage both in vitro (Fic et al, ; Skledar et al, ; Xin et al, ) and in vivo (Chen et al, ; Tiwari et al, ). There are not many studies comparing the genotoxic effects of bisphenol derivatives.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…DNA damage for bisphenols was seen in the order of BPS > BPF > BPA. Other researchers have also reported that BPA caused oxidative DNA damage both in vitro (Fic et al, ; Skledar et al, ; Xin et al, ) and in vivo (Chen et al, ; Tiwari et al, ). There are not many studies comparing the genotoxic effects of bisphenol derivatives.…”
Section: Discussionmentioning
confidence: 92%
“…The researchers concluded that BPA promoted cell survival following oxidative DNA damage after exposure to KBrO 3 . In another study, Chen et al () showed that cadmium exposure aggravated BPA‐induced genotoxicity and cytotoxicity through OGG1 inhibition in mouse embryonic fibroblast cell line (NIH3T3).…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescent dye DCFH-DA (2′,7′-dichlorofluorescein diacetate) assay was applied to examine cellular ROS level [ 48 50 ]. DCFH-DA will be hydrolysed by intracellular esterases to DCF.…”
Section: Meterials and Methodsmentioning
confidence: 99%
“…Cd binds sulfhydryl groups of proteins and glutathione (GSH) and especially GSH depletion results in increased production of reactive oxygen species (ROS) such as hydrogen peroxide, superoxide anion and hydroxyl radical [39-42]. Cr in contrast enters the redox cycle and acts as a catalyst of the Fenton reaction involving H 2 O 2 , leading to an increase in ROS production and alters erythrocyte membrane fluidity and integrity making erythrocytes more fragile and less osmotic resistant [40, 43].…”
Section: Discussionmentioning
confidence: 99%